The Porter stemming algorithm: then and now - Willett, Peter (Program : electronic library and information systems, 2006)
Purpose - In 1980, Porter presented a simple algorithm for stemming English language words. This paper summarises the main features of the algorithm, and highlights its role not just in modern information retrieval research, but also in a range of related subject domains.Design methodology approach - Review of literature and research involving use of the Porter algorithm.Findings - The algorithm has been widely adopted and extended so that it has become the standard approach to word conflation for information retrieval in a wide range of languages.Orinality value - The 1980 paper in Program by Porter describing his algorithm has been highly cited. This paper provides a context for the original paper as well as an overview of its subsequent use.